Short-term post-operative evaluation of young to middle age population following primary uncemented total hip arthroplasty - Parkar, Mehnaaz; Naser, Mohd A.; Patel, Mujtaba H.; Salve, Amol K.; Tupe, Pramod P.; Shaikh, Mujahidpasha (International Journal of Research in Orthopaedics, 2024)
Background: Total hip arthroplasty (THA) is the most commonly performed adult reconstructive procedure. The most common indication is severe osteoarthritis of the hip. THA remains the treatment of choice for restoring in end stage hip arthritis. It aims for immediate and long-lasting effects on pain and function in osteoarthritic hip. Methods: The study is a prospective observational study conducted on 30 patients enlisted in the inpatient department of orthopaedics at a rural tertiary health care centre (JIIU’S Indian Institute of Medical Sciences and Research, Warudi, Jalna). Only those patients satisfying the inclusion and exclusion criteria were included in the study. All the patients were explained about the surgical procedure, the purpose of the study and informed consent was taken. The patients were followed up at 1, 3 and 6-months post-operatively and the functional outcome was evaluated using Harris hip score and visual analogue scale (VAS). Results: Among the 30 cases included in the study, subjects were between 22 to 60 years of age. The cases were of either gender, with predominance of male cases. The mean Harris hip score and the mean pain score (VAS) at post-operative 1-month, 3-month and 6-month follow-ups improved significantly compared to their respective values at the pre-operative stage (p value <0.05 for all). Conclusions: The uncemented total hip replacement in young to middle-aged patients is an effective surgery which provides dramatic pain relief and excellent functional outcomes in majority of the subjects.